2021
DOI: 10.1016/j.isci.2021.102810
|View full text |Cite
|
Sign up to set email alerts
|

Applications of capillary action in drug delivery

Abstract: Contrary to the fact that capillary action is ubiquitous in our daily lives, its role in drug delivery has not attracted attention. Therefore, its application in medicine and disease treatment has not been actively developed. This perspective begins by reviewing the principles, advantages, and limitations of the three existing drug delivery strategies: non-covalent interaction, cavity loading, and covalent conjugation. Then, we discussed the principle of capillary action in drug delivery and the influencing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
(110 reference statements)
0
16
0
Order By: Relevance
“…Although metal organic salts, such as perylene‐3,4,9,10‐tetracarboxylic acid tetrapotassium salts, were introduced in early CVD studies [ 9,25 ] remarkable improvements in growth have been demonstrated by the adoption of alkali metal halides (AMHs). [ 26–38 ] The versatility and practicality of AMH‐assisted CVD are supported by the reduced process temperature, [ 26 ] millimeter‐scaled large grains, [ 27 ] rapid growth, [ 27,28 ] and one‐dimensional growth (TMD nanowire). [ 29 ] AMH‐assisted CVD has evolved into a universal process capable of synthesizing more than 40 2D TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…Although metal organic salts, such as perylene‐3,4,9,10‐tetracarboxylic acid tetrapotassium salts, were introduced in early CVD studies [ 9,25 ] remarkable improvements in growth have been demonstrated by the adoption of alkali metal halides (AMHs). [ 26–38 ] The versatility and practicality of AMH‐assisted CVD are supported by the reduced process temperature, [ 26 ] millimeter‐scaled large grains, [ 27 ] rapid growth, [ 27,28 ] and one‐dimensional growth (TMD nanowire). [ 29 ] AMH‐assisted CVD has evolved into a universal process capable of synthesizing more than 40 2D TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, hydrogels have been widely used as drug delivery vehicles due to their excellent biocompatibility, storage, this can result in depletion of the vehicles' drug content; concerning in vivo, this can manifest as burst release and systemic toxicity, which is especially problematic with ultrapotent drugs. [12][13][14][15] Given the advantages of hydrogels in biomedical engineering applications, if the above challenges of small hydrophilic molecule delivery are addressed, hydrogels could have an extensive clinical impact on the local delivery of small hydrophilic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17,18 ] To solve this problem, alkali metal halide‐based catalysts are commonly used to accelerate the growth of CVD 2D materials. [ 19 ] The role of cations (Na + , Li + , K + ) and anions (F − , Cl − , Br − , I − ), [ 20,21 ] and the use of single salt catalysts have been widely explored. [ 19,22–26 ] The metal halide catalysts offer two intermediate products including volatile metal oxyhalides and non‐volatile molten metals, assisting the nucleation growth's kinetics and thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] The role of cations (Na + , Li + , K + ) and anions (F − , Cl − , Br − , I − ), [ 20,21 ] and the use of single salt catalysts have been widely explored. [ 19,22–26 ] The metal halide catalysts offer two intermediate products including volatile metal oxyhalides and non‐volatile molten metals, assisting the nucleation growth's kinetics and thermodynamics. [ 20 ] In addition, dual additive catalysts with core precursor embedded – Na 2 MoO 4 –Na 2 SeO 3 have been introduced through a molten metal droplet growth pathway, resulting in a continuous growth of MoSe 2 monolayers.…”
Section: Introductionmentioning
confidence: 99%